The effect of bidder conservatism on M&A decisions: text-based evidence from US 10-K filings - Ahmed, Yousry; Elshandidy, Tamer (Elsevier, 2016)
This paper examines whether and how bidders' conservative tone in 10-K filings influences the subsequent mergers and acquisitions (M&A) investment decisions of these US firms from 1996 to 2013. Based on 39,260 firm-year observations, we find, consistent with behavioural consistency theory, that conservative bidders are less likely to engage in M&A deals. Further, those that decide to engage in M&As are likely to acquire public targets and within-industry firms. These bidders are inclined to employ more stock acquisitions than cash acquisitions. Our results also indicate that conservative bidders experience abnormally poor stock returns around the announcements of M&A investments. This provides new insights on the mechanism through which bidders' sentiments influence shareholders' wealth. Overall, these findings highlight the implications of the textual sentiment of corporate disclosure for the forecasting of corporate investment and financing decisions. Our results have practical implications, since they shed light on the value relevance of the information content of major Securities Exchange Commission (SEC)-mandated 10-K filings.